2002
DOI: 10.1177/152660280200900302
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Endovascular Abdominal Aortic Aneurysm Repair: Evaluation of a 277-Patient Single-Center Experience

Abstract: This study shows that not only is the number of procedures important to outcome, but also the frequency with which they are performed. Based on our team's performance data, 55 cases would appear to be the minimum volume and 1 case every 10 days the minimum frequency to obtain good operative results with aortic endografting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 26 publications
3
32
0
5
Order By: Relevance
“…Numerous interventional procedures, such as percutaneous coronary interventions, carotid artery stenting, endovascular aortic aneurysm repair, pulmonary valve implantation, and percutaneous balloon mitral valvuloplasty have evidence of a clear learning curve (31)(32)(33)(34)(35). The present study also shows that this is true for TAVI; a definite procedure-related learning curve was seen as evidenced by our decreased procedural and fluoroscopy times with reduced contrast volume and complications.…”
Section: Discussionsupporting
confidence: 67%
“…Numerous interventional procedures, such as percutaneous coronary interventions, carotid artery stenting, endovascular aortic aneurysm repair, pulmonary valve implantation, and percutaneous balloon mitral valvuloplasty have evidence of a clear learning curve (31)(32)(33)(34)(35). The present study also shows that this is true for TAVI; a definite procedure-related learning curve was seen as evidenced by our decreased procedural and fluoroscopy times with reduced contrast volume and complications.…”
Section: Discussionsupporting
confidence: 67%
“…LEE et al (22) in their experience concluded that the learning curve is important for the reduction of the perioperative complications, but doesn't influence the technical success of the procedure. LOBATO et al (23) have shown that 55 endovascular aneurysm repairs were necessary to achieve optimal results ; and that the interval between the procedures was also important, with one case every 10 days being the minimal workload to achieve these success rates. FORBES et al (24) in their analysis suggested that 60 elective endovascular repairs, or 20 with a specific device, are required to obtain optimal initial clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…In the conventional design, clinician investment may make them inclined to deliver other beneficial aspects of care more aggressively to patients receiving their preferred intervention. One can anticipate, in the EB design, that all clinicians will be aggressive in optimal management of their patients [4][5][6].…”
Section: Advantages Of the Eb Designmentioning
confidence: 99%